Stabilization of the classical phenotype upon integration of pancreatic cancer cells into the duodenal epithelium - Benedek Bozóky (Elsevier, 2021)
Introduction: Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive solid tumors. Based on transcriptomic classifiers, basal-like and classical PDAC subtypes have been defined that differ in prognosis. Cells of both subtypes can coexist in individual tumors; however, the contribution of either clonal heterogeneity or microenvironmental cues to subtype heterogeneity is unclear. Here, we report the spatial tumor phenotype dynamics in a cohort of patients in whom PDAC infiltrated the duodenal wall, and identify the duodenal epithelium as a distinct PDAC microniche. Materials and methods: We used serial multiplex quantitative immunohistochemistry (smq-IHC) for 24 proteins to phenotypically chart PDAC tumor cells in patients whose tumors infiltrated the duodenal epithelium. Additionally, we used a genetically engineered mouse model to study the PDAC cell phenotype in the small intestinal epithelium in a controlled genetic background. Result: We show that pancreatic cancer cells revert to non-destructive growth upon integration into the duodenal epithelium, where they adopt traits of intestinal cell differentiation, associated with phenotypical stabilization of the classical subtype. The integrated tumor cells replace epithelial cells in an adenoma-like manner, as opposed to invasive growth in the submucosa. Finally, we show that this phenomenon is shared between species, by confirming duodenal integration and phenotypic switching in a genetic PDAC mouse model. Discussion: Our results identify the duodenal epithelium as a distinct PDAC microniche and tightly link microenvironmental cue to cancer transcriptional subtypes. The phenomenon of “intestinal mimicry” provides a unique opportunity for the systematic investigation of microenvironmental influences on pancreatic cancer plasticity.